Membangun Literasi Keagamaan dan Sosial Masyarakat Melalui Dakwah Partisipatif Mahasiswa di Desa Tenggilis Kabupaten Pasuruan - Yaqin, Mukhamad Ainul; Jefriyanto, Jefriyanto (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service aims to develop religious and social literacy through participatory da’wah based on the Asset-Based Community Development (ABCD) approach in Tenggilis Village, Pasuruan Regency. The activities focused on active community involvement in religious programs such as Qur’anic literacy, Juz ‘Amma memorization, and Arabic language learning, as well as social initiatives like herbal gardens, communal clean-ups, and clean culture awareness. The students served as facilitators, assisting the community in identifying and developing local potential. The results of the service indicate that the ABCD approach effectively fostered communicative collaboration, strengthened the role of local religious figures, and encouraged sustainable initiatives such as the independent reinforcement of religious activities. This program successfully integrated Islamic values into the community’s social and spiritual practices in a contextual and participatory manner.